2021
DOI: 10.3390/fishes6040064
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Physiological Recovery after Capture by Hookline: The Case Study of the Blackspot Seabream (Pagellus bogaraveo)

Abstract: Evaluating the survival of discarded species is gaining momentum after the new European Common Fisheries Policy (Article 15 of the European Regulation No. 1380/2013). This regulation introduced a discard ban, with an exemption for those species with demonstrated high survival rates after their capture and release. Candidate species should be evaluated for each fishing gear and geographical area. In this study, we assessed not only survival, but also physiological recovery rates of blackspot seabream (Pagellus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 48 publications
3
9
1
Order By: Relevance
“…This evidence must be collected for each species, fishing gear and geographical area. Since then, there have been numerous studies focused on evaluating the survival of catches, including teleosts [ 20 , 21 , 22 ], elasmobranchs [ 23 , 24 ], cephalopods [ 25 ] and crustaceans [ 26 , 27 ]. Based on those studies, the European Commission approved the first exemption to this landing obligation (EU Commission Delegated Regulation 6794/2018) for Pagellus bogaraveo caught using the voracera fishing gear in the Strait of Gibraltar (SW Europe).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This evidence must be collected for each species, fishing gear and geographical area. Since then, there have been numerous studies focused on evaluating the survival of catches, including teleosts [ 20 , 21 , 22 ], elasmobranchs [ 23 , 24 ], cephalopods [ 25 ] and crustaceans [ 26 , 27 ]. Based on those studies, the European Commission approved the first exemption to this landing obligation (EU Commission Delegated Regulation 6794/2018) for Pagellus bogaraveo caught using the voracera fishing gear in the Strait of Gibraltar (SW Europe).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that capture by fishing is a challenging stressor to aquatic organisms [ 20 , 23 , 28 , 29 , 30 ], and that organisms must react through a series of physiological responses to overcome it. In vertebrates, primary stress responses include the release of catecholamines [ 31 ] and corticosteroids [ 28 , 32 ] to the bloodstream, cortisol being the most important corticosteroid in teleost fish [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations